The Translation Technique of Nouns Representing the Participants in the Subtitle Translation Film "The Conjuring 2: The Enfield Poltergeist" - Megan Asri Humaira, Rasmitadila , Rusi Rusmiati Aliyyah , Muhamad Aminulloh and Achmad Samsudin (International Journal of Advanced Science and Technology, 2020)
The purpose of this research is to know the translation techniques performed intranslating nouns representing participants. In conducting research used qualitativemethods with the technique of content analysis. With the data referred to, the clauses, inparticular, are nouns. The results of this study showed that the translation techniqueliterally dominated by a percentage of 49.5% compared to the use of other translationtechniques. The translation also follows its target language so that the content of the storyor meaning conveyed by the source text can be understood.